Impact Factor of the journals used by the post-graduation programs in Communication and Information for the propagation of knowledge - Almeida, Catia Candida de [UNESP]; Cabrini Gracio, Maria Claudia [UNESP]; Grossi de Carvalho, Angela Maria [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2018)
The management of scientific policy and its evaluation tools serve to plan and understand scientific dynamics. In this sense, the formulation of a policy for the evaluation of postgraduate courses is fundamental. Considering this problem, this research aims to describe the behavior of the impact factor values of the periodicals from the areas of Communication and Information, qualified by Qualis CAPES, for the evaluation of the scientific production of the postgraduate programs of the area, specifically, for the journals in the area of Communication and Information classified in group Al. The goal is to analyze their bibliometric indicators of impact, namely: Impact Factor and Quartile ranking. The results showed evidence of high variability of the values of the impact factor. The values of the IFs are related to the position of the quartiles, which remained unaltered for most journals in the analyzed period.
Keywords: Scientific journals; Impact Factor; Evaluation policy of postgraduate courses; Communication and Information